2016
DOI: 10.1193/012414eqs017m
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Structural and Nonstructural Building System Performance during Earthquakes: Part II – NCS Damage States

Abstract: Nonstructural components and systems (NCSs) provide little to no load bearing capacity to a building; however, they are essential to support its operability. As a result, 75–85% of the initial building financial investment is associated with these elements. The vulnerability of NCSs even during low intensity earthquakes is repeatedly exposed, resulting in large economic losses, disruption of building functionality, and concerns for life safety. This paper describes and classifies damage to NCSs observed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…Therefore, the force measurements in these bolts are expected to be insignificantly small (<< 1kN) unless the clamping force is exceeded by earthquake‐induced tension forces in these bolts. Additional details of the instrumentation of the test building and the elevator can be found in .…”
Section: Elevator Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the force measurements in these bolts are expected to be insignificantly small (<< 1kN) unless the clamping force is exceeded by earthquake‐induced tension forces in these bolts. Additional details of the instrumentation of the test building and the elevator can be found in .…”
Section: Elevator Systemmentioning
confidence: 99%
“…To the authors' knowledge, shake table testing of full‐scale guide rail counterweight subassemblies conducted in Taiwan is the only experimental investigation on elevator systems to date. For expansion of the experimental database, a landmark full‐scale five‐story reinforced concrete building, outfitted with a broad array of nonstructural components and systems, was tested on the large high‐performance outdoor shake table at the University of California, San Diego . Within this test building, a fully functional traction elevator was incorporated at full scale, allowing investigation of system‐level interactions between the building and the elevator as well as interactions between individual components of the elevator.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that the design target PIDR of about 2.5% was achieved during test FB-5, while well above the design target PIDR of 6% was attained during test FB-6. Interested readers may find additional information regarding the broader test program and results in [12][13][14].…”
Section: Shake Table Test Programmentioning
confidence: 99%
“…(UCSD) in 2012 [12][13][14]. Within this test building, for the first time, a prefabricated steel stair system was installed at full scale, allowing investigation of system-level interactions between the primary structure and the stairs as well as interaction between the stairs and other nonstructural components.…”
Section: Introductionmentioning
confidence: 99%
“…6 Similarly, extensive damage to NCSs in different facilities was reported after the 2011 off the Pacific coast of Tohoku earthquake, 7 and even in some cases, the loss of human life had been attributed to falling ceiling boards. Chen et al 9 and Pantoli et al 10 reported on a series of 1D shaking experiments on a full-scale, 5-story reinforced concrete building, conducted at the University of California, San Diego (UCSD) NEES site (NEES@UCSD). Recent Network for Earthquake Engineering Simulation (NEES) projects have focused on system-level response evaluation of NCSs on full-scale shake table experiments, to better understand their performance under seismic excitation.…”
mentioning
confidence: 99%